2018
DOI: 10.1002/cpt.1190
|View full text |Cite
|
Sign up to set email alerts
|

HLA Alleles and CYP2C9*3 as Predictors of Phenytoin Hypersensitivity in East Asians

Abstract: To develop a pre‐emptive genetic test that comprises multiple predisposing alleles for the prevention of phenytoin‐related severe cutaneous adverse reactions (SCARs), three sets of patients with phenytoin‐SCAR and drug‐tolerant controls from Taiwan, Thailand, and Japan, were enrolled for this study. In addition to cytochrome P450 (CYP)2C9*3, we found that HLA‐B*13:01, HLA‐B*15:02, and HLA‐B*51:01 were significantly associated with phenytoin hypersensitivity with distinct phenotypic specificities. Strikingly, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Different genetic and nongenetic factors predispose individuals to SCAR. The germline HLA alleles and CYP variants have been linked to SCAR, and some of the genetic markers have been translated to clinical applications to prevent the drug hypersensitivity reactions 8,12,14 . The functional studies further demonstrated that the associated HLA alleles possess increased affinity to the culprit drugs/metabolites 26,27 and drug-specific T cells serve the immunological basis of SCAR 18,28,29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different genetic and nongenetic factors predispose individuals to SCAR. The germline HLA alleles and CYP variants have been linked to SCAR, and some of the genetic markers have been translated to clinical applications to prevent the drug hypersensitivity reactions 8,12,14 . The functional studies further demonstrated that the associated HLA alleles possess increased affinity to the culprit drugs/metabolites 26,27 and drug-specific T cells serve the immunological basis of SCAR 18,28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Some of drug hypersensitivity reactions have shown HLA (human leukocyte antigen) genetic predisposition, e.g., HLA-B*15:02 for carbamazepine (CBZ)-induced SJS/TEN 5 , HLA-A*31:01 for CBZ-DRESS 6 , HLA-B*58:01 for allopurinol-SCAR 7,8 , HLA-B*13:01 for dapsone hypersensitivity 9,10 , and HLA-B*57:01 for abacavir hypersensitivity 11,12 . In addition to HLA, the genetic polymorphisms of drug metabolic enzyme CYP2C9 have been linked to phenytoin-induced SCAR 13,14 . However, both the HLA and CYP genetic variants have low positive predictive values (PPV) (e.g., the PPV of HLA-B*15:02 for CBZ-SJS/TEN is only 3%) 1,15 , suggesting that other factors are involved in the pathogenesis of SCAR.…”
Section: Introductionmentioning
confidence: 99%
“…By using GWAS approach, our previous study found that CYP2C9 * 3 was significantly related to PHT-induced SCARs in Han Chinese, Japanese and Malaysian, and by adding HLA-B*15:02 to this variant could increase sensitivity for preemptive test (35). In addition to HLA-B * 15:02, HLA-B * 13:01, and HLA-B * 51:01 were also found strong association with PHT-induced SCARs in Han Chinese, Thai and Japanese (37). Another genetic variant for PHT-induced SCARs was HLA-B * 15:13, which majorly found in Malaysian (24) (Table 1).…”
Section: Genetic Susceptibility To Aromatic Antiepileptic Drug-induced Severe Cutaneous Adverse Reactionsmentioning
confidence: 84%
“…The carriers of allelic variants of CYP2B6 T983C were in 4.2-fold higher risk to develop SJS/TEN due to low clearance of nevirapine (Ciccacci et al, 2013). Studies showed the variation in drug clearance enzyme CYP2C9*3 contributed to phenytoin-related SCARs with reduced drug clearance rate (Chung et al, 2014;Tassaneeyakul et al, 2016;Wu et al, 2018;Su et al, 2019;Sukasem et al, 2020b;Fohner et al, 2020), independently of HLA-B*15:02 risk allele. Glutathione-Stransferases (GST), which is a family of metabolic enzyme, plays a crucial role in the drug detoxification and activates some chemicals in a few cases.…”
Section: Genetic Variants and Sjs/ten Drug Metabolic Enzymes And Sjs/tenmentioning
confidence: 99%